Teaching Turkish-Islamic Scholars in Mobile Augmented Reality Environment: Its Effect on Students' Scientific Attitudes - Yıldırım, Pelin; Keçeci, Gonca (My University, 2023)
Science history showcases scientific thought's evolution and discoveries to students. Some topics include abstract concepts, making them challenging. Technology enhances teaching history of science, making it more effective and accessible. This study aims to examine the influence of teaching the lives of Turkish-Islamic scholars who have made significant contributions in various scientific disciplines such as astronomy, chemistry, and physics through TISAR-3D, a Mobile Augmented Reality (MAR) based learning environment, on secondary school students' scientific attitudes. A quasi-experimental method was employed in this study. This study was conducted in a public school in Elazığ, involving a total of 90 students in the 7th grade. Half of these students were assigned to the experimental group, while the other half formed the control group. The study was carried out for a duration of eight weeks on the experimental and control groups. The study lasted for eight weeks and consisted of an experiment group and a control group. The TISAR-3D application was used in the experiment group, while reading texts were used in the control group. The data obtained through the Scientific Attitude Scale were analyzed quantitatively using the SPSS 22 software package, and ANCOVA was applied. The study found that although the average scientific attitude scores of students in the experiment group, where the MAR application was used, were higher than the average scores of students in the control group, where reading texts were used, there was no statistically significant difference. Although primary textbooks are accessible to all students, insufficient coverage of Turkish-Islamic scholars and unfamiliarity with practical scholars may explain the lack of significant differences in scientific attitudes. Also, an eight-week study may not sufficiently alter students' scientific attitudes. By designing longer-term studies, a better understanding of how scientific attitudes develop and change over time can be achieved.
Keywords: Science Education; Mobile Augmented Reality; Secondary School Students; Science History; Turkish-Islamic Scholars; Scientific Attitude